DYSLEXIA – AN OVERVIEW OF ASSESSMENT AND TREATMENT METHODS - Evelin Witruk; Arndt Wilcke (Buletin Psikologi, 2010)
This article will give an overview of the different methods of assessment and treatment currently used in the field of dyslexia with a special focus on genetic research. Based on the modification and extension of the multilevel model of Valtin (1989, modified by Witruk, 1993b), assessment and treatment methods will be discussed due to their primary objectives. These methods will be described regarding primary causes (biological risk factors), secondary causes (partial performance deficits), primary symptoms (reading and writing problems) and secondary symptoms (emotional and behavioural disorders). Keywords: Multilevel model of dyslexia, genetics, magnocellular deficit, partial performance